EMD based statistical analysis of nighttime pre-earthquake ULF electric field disturbances observed by CSES - Yang, Bai-Yi; Li, Zhong; Huang, Jian-Ping; Yang, Xu-Ming; Yin, Hui-Chao; Li, Zong-Yu; Lu, Heng-Xin; Li, Wen-Jing; Shen, Xu-Hui; Zeren, Zhima; Tan, Qiao; Zhou, Na (Frontiers in Astronomy and Space Sciences, 2023)
To explore the correlation between earthquakes and spatial ultra-low frequency (ULF) electric field disturbances and to study the phenomenon of seismic ionospheric disturbances, this study uses three years of electric field ULF band data from 2019 to 2021 observed by the electric field detector carried by the CSES to identify anomalous disturbances using the anomaly automatic detection algorithm based on empirical mode decomposition (EMD) for the 2329 seismic events of magnitude not less than 5.0 and the electric field ULF disturbances in this period are analyzed by Superposed Epoch Analysis, and the statistical results are compared and analyzed in depth by earthquake location and different magnitudes in terms of both spatial and temporal scales and spatial distribution. The results show that: (1) There is a correlation between earthquakes of magnitude not less than 5.0 and ultra-low frequency disturbances in the electric field. The abnormal disturbance mainly occurred 11 days before the earthquake, 2 days before the earthquake to the day of the earthquake, and the location of the earthquake is within 200 km from the epicenter. (2) Sea earthquakes can observe more pre-seismic anomalous electromagnetic disturbances than land earthquakes. (3) In terms of earthquake magnitude, the larger the magnitude, the earlier the pre-earthquake anomalous disturbances appear and the wider the range of anomalies. This study provides an effective way to explain seismic ionospheric phenomena, and also provides a reference for the application of electromagnetic monitoring satellites in earthquake prediction and early warning as well as disaster prevention and mitigation.